Implementation of improved Perturb & Observe MPPT technique with confined search space for standalone photovoltaic system - Muhammad Kamran; Muhammad Mudassar; Muhammad Rayyan Fazal; Muhammad Usman Asghar; Muhammad Bilal; Rohail Asghar (Journal of King Saud University: Engineering Sciences)
Solar photovoltaic technology has been adopted by various global PV markets with 227 GW cumulative globally installed PV capacity in 2015 replacing the conventional fossil fuel energy resources. However, efficiency is still a big challenge for researchers and PV industry. This paper proposes a solar tracker and modified Perturb and Observe (P&O) algorithm for the standalone solar photo-voltaic system. Proposed algorithm confines the search space of the power curve to 10% area that contains Maximum Power Point (MPP) and starts perturbation and observation within that limited search space. The proposed P&O algorithm was simulated in MATLAB/Simulink. Solar tracker makes sure the availability of uniform and maximum irradiance to the solar module throughout the course of the sun during the day. Confinement of the algorithm’s search space lessened the response time to the changing weather conditions that in return decreases the steady-state oscillations at the MPP. Integration of the solar tracker and improved P&O MPPT algorithm provided the better quality and conditioned electricity to the load. The proposed system was experimentally steered whose results verified the effectiveness of the proposed P&O algorithm.